2011
DOI: 10.1007/s10681-011-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of avocado (Persea americana Miller) rootstocks selected under greenhouse conditions for tolerance to phytophthora root rot caused by Phytophthora cinnamomi

Abstract: Phytophthora cinnamomi, the causal agent of Phytophthora Root Rot (PRR) of avocado, is the most serious disease of avocado worldwide. The development of tolerant rootstocks to control PRR has proven to be an effective means to control the disease. However, using traditional breeding approaches can take over a decade to produce results and there has been a limited use to integrate molecular data into breeding efforts. Therefore, the objective of this work was to use amplified fragment length polymorphism (AFLP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…The evaluation of their morphological characters is inaccurate due to the influence of environmental factors, subjectivity, and a limited number of discriminating traits (Alcaraz and Hormaza, 2007). Consequently, avocado characterization and diversity studies have been strengthened by analyses of genetic markers including isozymes (Torres and Bergh, 1978), minisatellites (Mhameed et al, 1997), random amplified polymorphic DNA (RAPD) (Fiedler et al, 1998), restriction fragment length polymorphism (RFLP) (Davis et al, 1998), single sequence repeats (SSRs) (Ashworth and Clegg, 2003;Schnell et al, 2003;Alcaraz and Hormaza, 2007;Kwame et al, 2008;Gross-German and Viruel, 2013), amplified fragment length polymorphism (AFLP) (Douhan et al, 2011;Cañas-Gutierrez et al, 2015), and single nucleotide polymorphism (SNP) (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of their morphological characters is inaccurate due to the influence of environmental factors, subjectivity, and a limited number of discriminating traits (Alcaraz and Hormaza, 2007). Consequently, avocado characterization and diversity studies have been strengthened by analyses of genetic markers including isozymes (Torres and Bergh, 1978), minisatellites (Mhameed et al, 1997), random amplified polymorphic DNA (RAPD) (Fiedler et al, 1998), restriction fragment length polymorphism (RFLP) (Davis et al, 1998), single sequence repeats (SSRs) (Ashworth and Clegg, 2003;Schnell et al, 2003;Alcaraz and Hormaza, 2007;Kwame et al, 2008;Gross-German and Viruel, 2013), amplified fragment length polymorphism (AFLP) (Douhan et al, 2011;Cañas-Gutierrez et al, 2015), and single nucleotide polymorphism (SNP) (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their efficacy has yet to be tested for use in identifying tolerant rootstocks, but it is known that they amplify across all avocado varieties and can be used for investigation of genetic relations [ 34 , 35 ]. The University of California Riverside (UCR) has recently employed 61 polymorphic AFLP markers to characterise PRR tolerance in 83 rootstocks from various locations including South Africa and Israel with the majority of rootstocks from the UCR collection [ 36 ]. The study concluded that resistance mechanisms vary between tolerant cultivars and no trend was observed in the cluster analysis.…”
Section: Introductionmentioning
confidence: 99%
“…and Phytophthora cinnamomi Rands. are potentially limiting, being P. cinnamomi the most devastating oomycete in avocado commercial crops (GEORGE 1956, GABOR 1991, DOUHAN ET AL. 2011.…”
Section: Introductionmentioning
confidence: 99%